Upper crustal deformation in continent‐continent collision: A case study from the Bernard nappe complex (Valais, Switzerland). Issue 5 (3rd October 2013) - Scheiber, Thomas; Adrian Pfiffner, O.; Schreurs, Guido
Abstract [1] The Penninic nappes in the Swiss Alps formed during continental collision between the Adriatic and European plates in Cenozoic times. Although intensely studied, the finite geometry of the basement‐bearing Penninic nappes in western Switzerland has remained a matter of debate for decades (e.g., "Siviez‐Mischabel dilemma") and the paleogeographic origin of various nappes has been disputed. Here, we present new structural data for the central part of the Penninic Bernard nappe complex, which contains pre‐Permian basement and Permo‐Mesozoic metasedimentary units. Our lithological and structural observations indicate that the discrepancy between the different structural models proposed for the Bernard nappe complex can be explained by a lateral discontinuity. In the west, the presence of a Permian graben caused complex isoclinal folding, whereas in the east, the absence of such a graben resulted mainly in imbricate thrusting. The overall geometry of the Bernard nappe complex is the result of three main deformation phases: (1) detachment of Mesozoic cover sediments along Triassic evaporites (Evolène phase) during the early stages of collision, (2) Eocene top‐to‐the‐N(NW) nappe stacking (Anniviers phase), and (3) subsequent backfolding and backshearing (Mischabel phase). The southward localized backshearing is key to understand the structural position and paleogeographic origin of units, such as the Frilihorn and Cimes Blanches "nappes" and the Antrona ophiolites. Based on these observations, we present a new tectonic model for the entire Penninic region of western Switzerland and discuss this model in terms of continental collision zone processes.